2022
DOI: 10.3390/polym14081523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of GFRP Laminates Exposed to Thermal and Moist Environmental Conditions: Experimental and Model Assessment

Abstract: This paper presents an experimental and analytical study about the mechanical response at a different temperature on glass fiber-reinforced polymer laminates. The effect of different environmental conditions on compressive, tensile, stiffness, and viscoelastic behavior (storage modulus, loss modulus and damping ratio) of laminates were investigated. Before testing, laminates were preserved in a deep freezer at −80 °C, −20 °C, 0 °C, and room temperature (25 °C) for up to 60 days. Results confirmed that temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The results showed that temperature had the greatest effect on the deterioration of tensile strength in GFRPs, followed by exposure time 18 . Similarly, another study using ANOVA tables on tensile tests performed on GFRP laminates at temperatures ranging from −80°C to 100°C found that temperature had a statistically significant contribution and should be considered when evaluating the tensile strength properties of GFRP materials under varying temperatures 20 . As can be seen, regression and ANOVA analysis play a critical role in determining mechanical parameters.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The results showed that temperature had the greatest effect on the deterioration of tensile strength in GFRPs, followed by exposure time 18 . Similarly, another study using ANOVA tables on tensile tests performed on GFRP laminates at temperatures ranging from −80°C to 100°C found that temperature had a statistically significant contribution and should be considered when evaluating the tensile strength properties of GFRP materials under varying temperatures 20 . As can be seen, regression and ANOVA analysis play a critical role in determining mechanical parameters.…”
Section: Resultsmentioning
confidence: 86%
“…19 Tefera et al analyzed the tensile and compression properties of GFRP laminates under thermal and moist environmental conditions using analysis of variance. 20 The highest tensile stress and stiffness response of laminates were observed at the 0 C test. Then, tensile stresses were reduced by 27.24%, 53.28%, 239.39%, and 1596.28% when the temperature increased from the 0 C to 100 C test.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is important to know the compressive and tensile behaviour of FRP materials before using them for composite structures. Particularly, the flexural behaviours of glass- and carbon-reinforced hybrid epoxy composite laminates were investigated extensively under room temperature tests in [ 14 , 15 , 16 , 17 ]. The flexural and tensile moduli of hybrid composite laminates were decreased as the hybrid ratio increased [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%